1985
DOI: 10.1111/j.1600-0447.1985.tb05045.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of questionnaires in population studies on drug use

Abstract: The concurrent validity of questionnaires in population studies on drug use was tested by comparing information from registers and interviews in two populations of young people from Gothenburg. The questionnaire items' sensitivity and specificity according to criteria and their capacity for prediction of drug use and no drug use and correct classification were calculated. Considering criteria weaknesses and other sources of errors, the validity of the questionnaire items was good. This conclusion is basic to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 10 publications
2
28
0
1
Order By: Relevance
“…Benson and Holmberg assessed the validity in the Gothenburg part of the same national conscription survey and found that conscripts generally gave correct information concerning drug use and abuse. 19 Rydelius compared data on alcohol consumption obtained by structured in depth interviews of 1004 18 year olds and data obtained anonymously from the same group in the conscription survey during the same year and found a good correlation.20 The strong association between the reported alcohol consumption at conscription and the incidence of treatment for alcoholism during follow up lends further support to the assumption that the selfreported level ofalcohol consumption in this cohort was reliable.…”
Section: Discussionmentioning
confidence: 88%
“…Benson and Holmberg assessed the validity in the Gothenburg part of the same national conscription survey and found that conscripts generally gave correct information concerning drug use and abuse. 19 Rydelius compared data on alcohol consumption obtained by structured in depth interviews of 1004 18 year olds and data obtained anonymously from the same group in the conscription survey during the same year and found a good correlation.20 The strong association between the reported alcohol consumption at conscription and the incidence of treatment for alcoholism during follow up lends further support to the assumption that the selfreported level ofalcohol consumption in this cohort was reliable.…”
Section: Discussionmentioning
confidence: 88%
“…Under-reporting of problematic alcohol and cannabis use could lead to underestimation of relative risks for adult alcohol and drug abuse. Although Benson & Holmberg found that conscripts generally gave correct information concerning problematic alcohol and cannabis use [44], we still do not know how representative are the habits reported at conscription for the follow-up period. In this study, the habits at a young age have to be regarded as predictors for the longitudinal perspective.…”
Section: Discussionmentioning
confidence: 97%
“…28 Consequently, self-reported cannabis use is likely subject to under-reporting. On the contrary, studies of the same group of Swedish conscripts have shown that the young men generally gave correct information on their drug use, 29 suggesting that the material is valid for epidemiological analysis. Because this study only included men in Sweden born around 1950, the generalizability is limited.…”
Section: Discussionmentioning
confidence: 98%